Record-Breaking Steric Crowding in Trialkylamines Prepared by Oxidative Ring Opening - Banert, Klaus; Heck, Manuel; Ihle, Andreas; Michael, Erik; Weber, Richard (Synthesis, 2020)
Epoxidation of olefinic heterocyclic amines and subsequent acid-catalyzed hydrolysis or alternatively the direct dihydroxylation with the help of osmium tetroxide led to diols, which underwent ring cleavage in the presence of lead tetraacetate to give 3-isopropyl-2,2,4,4-tetramethyl-3-azahexanedial and 3-tert-butyl-2,2,4,4-tetramethyl-3-azapentanedial. Whereas the former dialdehyde is a highly unstable model compound because of a rapid intramolecular aldol reaction, the latter product proves to be isolable at room temperature. Furthermore, this compound is the first open-chain tri-tert-alkylamine establishing in a new record of steric crowding in tertiary amines. Strong tendencies to a Hofmann-like elimination reaction or to ring-closing reactions were observed when the aldehyde units of 3-tert-butyl-2,2,4,4-tetramethyl-3-azapentanedial were transformed into other functionalities, since both types of reactions led to a significantly decrease of the steric stress.
Keywords: amines; nitrogen heterocycles; olefin oxidation; ring cleavage; steric hindrance